Analyses Des Représentations Des Apprenants De Tronc Commun Marocain En Interactions Mécaniques (3éme Loi De Newton) - Cas De La Direction Provinciale De L’education Nationale De Settat - Naoual Nasser; Mustapha El Khouzai; Mohamed Taoufik (European Scientific Journal, ESJ, 2018)
The purpose of this study is to analyze the misconceptions encountered in mechanics by the Moroccan students, aged 14-16, particularly the common core, the first year of Moroccan high-school, and most notably that of the mechanical interactions (Newton's third law) so that teachers can take them into account in their teaching. A questionnaire is administered to students from four high schools within the Provincial Directorate of Settat, Morocco (350 students’) just before the mechanical interactions course. The results show that the difficulties encountered when learning this course are due to misconceptions. Indeed, the relation between the forces and the objects on which we act is not well understood for students: they believe that the force is a property of unique objects and not a relation between objects. Also, the students’ reasoning seems to be strongly influenced by the context of the proposed situation (nature of the objects, their situation and their dynamics).